ANALISIS KONTRIBUSI PAJAK DAERAH SERTA PROSPEKNYA TERHADAP PENDAPATAN ASLI DAERAH KOTA SAMARINDA - ISMAWATI PUTRI; Cornelius Rantelangi; Raden Priyo Utomo (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
This research aims to determine the contribution of regional tax to regional income for the year 2012 to 2016 and the prospect of regional tax contribution to regional income for the years 2017 to 2021. Type of this research is descriptive research using secondary data sources. Secondary data is using the data target and realization of regional income and regional tax at period of 2012 to 2016. Analytical tools used in this research are the analysis of contributions and time series (single moving averages) analysis. Based on the results of the research indicates that the contribution of regional tax to regional income of the city of Samarinda for 2012 to 2016 is including very good criteria because of the average of contribution is 50% and the result is 57.12%. It also happened at the period of 2017 to 2021, where the prospect of regional tax contribution to regional income of Samarinda contains the very good criteria with an average of contribution is 57.57%. So it can be said that the regional tax is one of the biggest contributors in increasing of regional income of  Samarinda City.